Wavelength coded volume holographic gratings based dual wavelength fluorescence imaging system - Chia, Yu-Hsin; Huang, Yi-You; Luo, Yuan (SPIE, 2021)
We present a wavelength coded volume holographic gratings (WC-VHGs) based dual wavelength fluorescence imaging system to simultaneously obtain two color fluorescence images of biological samples in one shot. The system utilizes wavelength coded recording technique based on Bragg degeneracy to generate the PQ-PMMA volume holographic gratings, which has high selectivity in both wavelength and angle. In order to improve the optical sectioning ability of the proposed system, we use HiLo image processing to suppress the out of focus signal. Experimental results demonstrate the imaging ability of the proposed system to observe multi-wavelength fluorescence images and HiLo images.